Assessment of Posterior Maxillary Alveolar Bone for Immediate Implant Placement: A Quantitative and Qualitative Analysis - Alkhames, Hussain M.; Ali, Ramy Moustafa Moustafa; Alzouri, Sukinah Sameer; Bayome, Mohamed (European Journal of Dentistry, 2024)
Objectives The aims of this study were to evaluate posterior maxillary alveolar bone dimensions and to compare these dimensions in males and females.Materials and Methods The sample consisted of 102 cone beam computed tomography (CBCT) images for 62 male patients (mean age 29.92 ± 9.04 years) and 40 female patients (mean age 29.70 ± 9.54 years). Four distances and three densities were measured; a multivariate analysis of variance and Mann–Whitney's U test were applied to compare the differences between sexes.Results For the first maxillary molar, there were significant differences between males and females in terms of coronal width (13.95 ± 1.31 and 13.22 ± 1.159 mm, respectively) and middle width (14.28 ± 1.43 and 13.57 ± 1.478 mm, respectively). However, no significant difference was found regarding height (7.93 ± 3.8 mm for both) or apical width (14.68 ± 2 mm for both). Regarding the second maxillary molar, significant differences between males and females were found in terms of coronal width (14.66 ± 1.63 and 13.54 ± 1.512 mm, respectively), middle width (14.35 ± 1.825 and 13.25 ± 1.52 mm, respectively), and height (7.29 ± 3.00 and 8.66 ± 3.16 mm, respectively), whereas the gender dimorphism regarding apical width had borderline significance (14.09 ± 1.731 mm; p = 0.048). No significant differences were found regarding density.Conclusion The minimum average alveolar bone height for the second maxillary molar region was 7.29 ± 30 mm with significant gender dimorphism. Therefore, CBCT scans should be recommended prior to immediate implant placement.
Keywords: immediate implant; maxillary bone; maxillary molars; bone height; bone density; CBCT